Impact Socio-Environnemental De L’exploitation Du Palmier À Huile (Elaeis Gineensis) En Lodjukru Dans La Région De Dabou (Côte d’Ivoire) - Siméon, Akmel Meless (European Scientific Journal, ESJ, 2018)
The operation of the oil palm tree is taking a global scale. In Ivory Coast, people are more involved in the activity because of its importance. The hypothesis of Lodjukru (Snipe region) is for this eloquent purpose, because large areas of oil palms (Traditional, selected) are perceptible everywhere. These are the cases observed in Jasakp, Dibrm and Armɛbɛ, which is our field of investigation. The study (qualitative and quantitative) identified the different stages and explained the determinants (socioeconomic value) of the operation of the oil palm tree. It also described and analyzed the environmental problems and health risks associated with the activity.